2003
DOI: 10.1002/cne.10532
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PTPRO during mouse development suggests involvement in axonogenesis and differentiation of NT‐3 and NGF‐dependent neurons

Abstract: Competition and cooperation between type II and type III receptor protein tyrosine phosphatases (RPTPs) regulate axon extension and pathfinding in Drosophila. The first step to investigate whether RPTPs influence axon growth in the more complex vertebrate nervous system is to identify which neurons express a particular RPTP. We studied the expression of mouse PTPRO, a type III RPTP with an extracellular region containing eight fibronectin type III domains, during embryogenesis and after birth. Mouse PTPRO mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
57
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 53 publications
9
57
0
Order By: Relevance
“…PTP-␦, PTP-, and LAR bind to the liprin protein family, which is implicated in several aspects of synapse formation (Serra-Pages et al, 1995;Zhen and Jin, 1999;Kaufmann et al, 2002;Wyszynski et al, 2002). Substrates for PTPRO may include Trk receptors (Beltran et al, 2003), in addition to the novel neural protein NPCD (neuronal pentraxin with chromo domain) (Chen and Bixby, 2005a,b). More progress has been made in the discovery of potential substrates for LAR; it can act together with Abl to coordinate phosphorylation/dephosphorylation of the profilin-interacting protein Ena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTP-␦, PTP-, and LAR bind to the liprin protein family, which is implicated in several aspects of synapse formation (Serra-Pages et al, 1995;Zhen and Jin, 1999;Kaufmann et al, 2002;Wyszynski et al, 2002). Substrates for PTPRO may include Trk receptors (Beltran et al, 2003), in addition to the novel neural protein NPCD (neuronal pentraxin with chromo domain) (Chen and Bixby, 2005a,b). More progress has been made in the discovery of potential substrates for LAR; it can act together with Abl to coordinate phosphorylation/dephosphorylation of the profilin-interacting protein Ena.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore chose to examine regulation of motor axon growth in the chick lumbosacral spinal cord. Two type IIa RPTPs, PTP-␦ and PTP-, and one type III RPTP, PTPRO, are expressed during the period of axon outgrowth in motor columns of the rodent spinal cord and the chick brachial spinal cord (Yan et al, 1993;Sommer et al, 1997;Chilton and Stoker, 2000;Beltran et al, 2003;Thompson et al, 2003). To determine whether these RPTPs are also expressed in chick lumbosacral motor neurons, we performed in situ hybridization using digoxygenin-labeled riboprobes.…”
Section: Rptps Are Expressed In the Lateral Motor Column Of The Embrymentioning
confidence: 99%
“…Here, the combinations of R3 RPTPs and substrate RPTKs are important in vivo, because a RPTP dephosphorylates a substrate RPTK only when they are expressed in the same cell. Ptpro is preferentially expressed in the nervous system and kidney (22), and expression of Ptprb is restricted to endothelial cells (23). Ptprj is broadly expressed in various cell types, including endothelial, epithelial, hematopoietic, and neuronal cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other genes including those of the cytochrome P450 family exhibited expression changes, not surprising in the light of their role in xenobiotic metabolism. The study also identified a number of novel genes including a protein tyrosine phosphatase, which is thought to play a role in cell growth and differentiation, 13 and is presumably induced in response to CCl 4 -induced liver injury. The data correlate nicely with independent approaches, and extend those observations by affording new information.…”
mentioning
confidence: 99%